Spausdinto žodžio autoritetas XIX a. Lietuvos kaime - Maskoliūnienė, Džiuljeta (Knygotyra, 2005)
Gutenberg's revolutionary discovery contributed to the modernization and democratization processes of Western Europe. "In social respect typographic continuity of man brought nationalism, mass market, universal literacy, and education," states M. McLuhan. Despite obvious unfavorable circumstances, which emerged in Lithuania in the 19th century as well as in Western Europe, both society and culture started to democratize. Figuratively speaking, the Enlightenment epoch was dwelling in the air at the moment, where the printed word, the book phenomenon, occupied a very special place. It was a new form of indirect public communication for the Lithuanian peasant, which he was destined to know, "to tame" in the course of the 19th century.It is of consequence that the book, having acquired a mass, cheaper and in this sense a more affordable form, moreover, printed in the comprehensible Lithuanian language, spreads among people and becomes an evident fact of culture participation in society. The book gains authority. V. Kavolis, reasoning the issue where the authority of culture originates (the book—a concurrent attribute of culture), raises the following topical aspects: 1) "some elements of culture become reliable, important to human behavior," 2) "the authority of culture can originate from the power of its structure and its coherence. We feel striking power which is in the very text or rite of culture." In the educative 19th century, there are plenty of signs recording the significance and power of the book. For example, already at the beginning of the century, the book as a significant tool of education was poetized in the texts by Dionizas Poška. In "Gramatoje pas Tadeušą Čackį," Dionizas Poška emphasizes the importance of the trilingual dictionary by K. Sirvydas, deplores the fate of many of the copies of the book, and grieves for trampling the mother tongue.It is of major importance that the peasant estate becomes aware of the authority of the book. In general, in the epoch of Enlightenment, the peasant's topic arises (the peasant becomes an object of literary portrayal as well). Interaction with the printed text (a prayer book, hymnal, fiction, calendar, map) turns into a new form of communication. It is prestigious for a richer farmer to have a book at home.The increase in the standing of the book and reading is directly linked with the rise of the school system.Partially, Lithuania reflects general European consistent patterns: "the majority of European regions, assuredly, so to say, and finally, became alphabeticized only in the 19th century, when primary schools were established wide," the "History of European Mentality" admits. The major mission of schools in that period was alphabetization. It could not have been efficient without printed books, without "a uniformly formalized educational process" (McLuhan).Surely, the most traditional area of the operation of the printed word is the Church. Prayer books and other religious publications did not require much promotion; they were willingly bought. The ability to read was rather limited for the major part of the population. They could read only "their own" prayer book, that is, the book they were taught to read (A. Kulakauskas). It is obvious that literature of religious origin performed a certain educational role, which later was taken over by primers.The publishing of Lithuanian books was not limited only to confessional or educational editions. Fiction books and books of practical attribution intended for peasant readers were started to publish in Lithuania. This is a major distinction. Buying books of the latter attribution was absolutely a voluntary, cultural gesture not supervised by any institution. This reveals the then state of literary communication in Lithuania. Gradually, the peasant's self-consciousness of the 19th century changed; there were more people who could read not only prayer books but who preferred reading for their own pleasure. There occurred the need to read books not because it was a duty or it was profitable, but because books could meet more specific needs. The peasant finds it pleasant to read and experiences some aesthetic feelings. The practice of reading "Saints' Lives" embodied these qualities already earlier. Now it is set much on reading translations of foreign authors or books by Lithuanian authors—P. Arminas, S. Daukantas, M. Valančius, or fiction by other authors.Undoubtedly, the spread of the Lithuanian printed word in the Lithuanian village is a significant token of the 19th century, never suppressed by the wrongful prohibition of Lithuanian press by Czar Russia in 1864.